Antifibrogenic effects of C‐C chemokine receptor type 2 antagonist in a bleomycin‐induced scleroderma model. Issue 1 (11th March 2020) - Ishikawa, Masato; Yamamoto, Toshiyuki
Abstract: There have been several studies on the role of the monocyte chemotactic protein‐1/C‐C chemokine receptor type 2 (CCR2) signalling pathway in fibrotic diseases, which identified the blockade of this pathway as a potential therapeutic target for treating fibrosis. We examined the efficacy of CCR2 antagonist (RS‐504393) in a mouse model of scleroderma induced by bleomycin. RS‐504393 was administered via intradermal injection 6 hours prior to bleomycin injection, in the same sites. Histopathological examination showed that RS‐504393 treatment suppressed dermal fibrosis and decreased dermal thickness. The numbers of mast cells and myofibroblasts in the skin of RS‐504393–treated mice were significantly lower compared with those in PBS‐treated mice. Moreover, the amount of collagen in the skin of RS‐504393–treated mice was significantly lower compared with that in the PBS‐treated mice. Additionally, mRNA levels of TGF‐β1 and collagen I alpha 1 in sclerotic skin were significantly decreased by RS‐504393, and semiquantitative histopathological scoring of the lungs showed inhibition of fibrosis in RS‐504393–treated mice. The amount of collagen in the lung of the RS‐504393–treated mice was lower compared with that in the PBS‐treated mice. These data suggest that CCR2 antagonist RS‐504393 may be a therapeutic agent for human scleroderma.